2018
DOI: 10.1111/risa.13181
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effectiveness of Respiratory Protective Devices in Reducing Influenza Outbreak

Abstract: Outbreaks of influenza represent an important health concern worldwide. In many cases, vaccines are only partially successful in reducing the infection rate, and respiratory protective devices (RPDs) are used as a complementary countermeasure. In devising a protection strategy against influenza for a given population, estimates of the level of protection afforded by different RPDs is valuable. In this article, a risk assessment model previously developed in general form was used to estimate the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 32 publications
0
46
0
2
Order By: Relevance
“…Yan et al (90) provide an additional example of an incremental impact assessment of respiratory protective devices using an augmented variant of a traditional SIR model in the context of influenza with N95 respirators. They showed that a sufficiently high adherence rate (~80% of the population) resulted in the elimination of the outbreak with most respiratory protective devices.…”
Section: Estimating Population Impactsmentioning
confidence: 99%
“…Yan et al (90) provide an additional example of an incremental impact assessment of respiratory protective devices using an augmented variant of a traditional SIR model in the context of influenza with N95 respirators. They showed that a sufficiently high adherence rate (~80% of the population) resulted in the elimination of the outbreak with most respiratory protective devices.…”
Section: Estimating Population Impactsmentioning
confidence: 99%
“…Yan et al (43) provide an additional example of an incremental impact assessment of respiratory protective devices using an augmented variant of a traditional SIR model in the context of influenza with N95 respirators. They showed that a sufficiently high adherence rate (~80% of the population) resulted in the elimination of the outbreak with most respira-tory protective devices.…”
Section: Population Impactmentioning
confidence: 99%
“…El estudio de Yan y colaboradores estimó una reducción en la incidencia acumulada de enfermedad respiratoria de alrededor de 20%, asumiendo que de 10 a 15% de la población utiliza cubrebocas de filtrado medio o respiradores N95. 22 El estudio de Brienen y colaboradores estimó que 40% de la población tendría que utilizar cubrebocas quirúrgicos de manera perfecta (eficacia de 70%) para reducir el número de reproducción de influenza de 2.0 a 1.5; sin embargo, si 40% de la población utilizara cubrebocas con una eficiencia de 30%, el número de reproducción disminuiría de 2.0 a 1.8. 23 Finalmente, el estudio de Tracht y colaboradores concluye que los cubrebocas quirúrgicos muestran un efecto pequeño sobre la probabilidad de contagio, y su efecto durante una epidemia no sería relevante.…”
Section: Uso Masivo De Cubrebocas En La Población Generalunclassified